2006
DOI: 10.1016/j.optcom.2006.02.056
|View full text |Cite
|
Sign up to set email alerts
|

Three level atom optics in dipole traps and waveguides

Abstract: An analogy is explored between a setup of three atomic traps coupled via tunneling and an internal atomic three-level system interacting with two laser fields. Within this scenario we describe a STIRAP like process which allows to move an atom between the ground states of two trapping potentials and analyze its robustness. This analogy is extended to other robust and coherent transport schemes and to systems of more than a single atom. Finally it is applied to manipulate external degrees of freedom of atomic w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 39 publications
0
73
0
Order By: Relevance
“…Stimulated Raman adiabatic passage (STIRAP) has been widely studied for population transfer of molecules [39][40][41][42][43][44][45][46], transport of single atoms [47][48][49][50][51][52], electrons [53,54], and BECs [55][56][57][58]. The remarkable properties of this protocol have already been demonstrated in diverse areas such as chemical reaction dynamics [59], laser-induced cooling of atomic gases [60], light beams propagating in three evanescently coupled optical waveguides [61][62][63][64], sound propagation in sonic crystals [65], and control of a superconducting qubit [66].…”
Section: B Spin-selective Stirapmentioning
confidence: 99%
“…Stimulated Raman adiabatic passage (STIRAP) has been widely studied for population transfer of molecules [39][40][41][42][43][44][45][46], transport of single atoms [47][48][49][50][51][52], electrons [53,54], and BECs [55][56][57][58]. The remarkable properties of this protocol have already been demonstrated in diverse areas such as chemical reaction dynamics [59], laser-induced cooling of atomic gases [60], light beams propagating in three evanescently coupled optical waveguides [61][62][63][64], sound propagation in sonic crystals [65], and control of a superconducting qubit [66].…”
Section: B Spin-selective Stirapmentioning
confidence: 99%
“…An example of the waveguide potentials resulting from this model for 6 Li atoms and for experimentally realistic parameters is shown in Fig. 2.…”
Section: Atom Chipsmentioning
confidence: 99%
“…Our simulations start out with a single 6 Li atom which is initially located in the left waveguide. Its transversal wave function corresponds to the ground state of the potential in the transversal direction (determined numerically) and longitudinally we assume a Gaussian profile of similar width.…”
Section: D Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This adiabatic transport process is the matter-wave analog of the very well-known quantum optical stimulated Raman adiabatic passage (STIRAP) technique [11], and it is based on adiabatically following an energy eigenstate of the system, the so-called spatial dark state, that, ideally, only involves the vibrational ground states of the two extreme wells. Extensions of these TLAO techniques to atomic wave packets in dipole waveguides [12], to Bose-Einstein condensates [13], to the transport of electrons in quantum-dot systems [14], and to superconductors [15], were performed later. Even very recently, by exploiting the wave analogies between classical and quantum systems, Longhi et al [16] have experimentally reported light transfer in an engineered triple-well optical waveguide by means of the classical analog of the matter-wave STIRAP.…”
Section: Introductionmentioning
confidence: 99%